Habib dalam Pemaknaan Generasi Milenial eks-Simpatisan Front Pembela Islam Pasuruan - Jafar, Jafar (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2024)
This study focuses on the meaning of the millennial generation who are former FPI Pasuruan sympathizers on the meaning of habib. This research is motivated by habib's position as a charismatic figure. They occupy a central role, because they are placed as "multiplayer" who can create discourse in society, especially in terms of religion. Of course, theologically, the privilege of a habib can be justified through the doctrine of the continuity of the nasab with the Prophet Muhammad. However, in the realm of reality, support for a particular habib is not directly proportional to support for another habib. This is as shown by the millennial generation who are former FPI Pasuruan sympathizers. This research produced three typologies related to their interpretation of habib. First, it is a group that considers habib as a noble person who should not be criticized. Second, habib as an ordinary human being who has the potential to be guilty. The third group assessed that the point of difference was not in the issue of nasab (habib) but in the side of piety.